Feasibility Study And Business Planning Of Rumahmakan.Online Digital Menu Whatsapp Ordering System - Lesmana, Fanji; Turgarini, Dewi (Universitas Pendidikan Indonesia, 2021)
Food delivery service business have increased rapidly in the era of the Covid-19 pandemic. People use new business model devices in their daily lives. E-commerce/platform of food delivery service is an integrated business system that started from the food provider to the food buyers. Â Commonly, the food delivery service platform set the